Patterned photonic crystals for hiding information. Issue 19 (26th April 2017) - Li, Yanan; Zhou, Xue; Yang, Qiang; Li, Yudong; Li, Wenbo; Li, Huizeng; Chen, Shuoran; Li, Mingzhu; Song, Yanlin
Abstract : A prototype design for hiding messages in photonic crystals was developed by building a coding relationship between optical stopbands and information units. Abstract : Coding techniques are not only a popular strategy for information recording and communication, but also an efficient strategy for information protection. Many species in nature, such as chameleons and peacocks, demonstrate brilliant colourful appearances for camouflage, courtship or communication. The unique optical property that originates from the interaction of light with the periodic nanostructures on their surfaces, known as photonic crystals (PCs), provides an attractive candidate for coding and anti-counterfeiting. Here we present a prototype design for hiding information in photonic crystals by building a coding and encryption relationship between optical stopbands and information units. The hidden messages are protected by three different defense strategies: characteristic optical stopbands, algorithm encryption and angle-dependent encryption, which could dramatically improve the security level of the hidden information. In combination with the large coding capacity, inherent optical stability and robust fabrication process, this PC coding system has great potential for secure information storage and communication, anti-counterfeiting and massively parallelized sensors.